The Transumbilical Laparoendoscopic Single-Site Extraperitoneal Approach for Pelvic and Para-Aortic Lymphadenectomy: A Technique Note and Feasibility Study - Peng, Shiyi; Zheng, Ying; Yang, Fan; Wang, Kana; Chen, Sijing; Wang, Yawen (Frontiers in Surgery, 2022)
Background：Nowadays, the lymphadenectomy could be performed by the transperitoneal or extraperitoneal approach. Nevertheless, each approach has its own advantages and disadvantages. For lymphadenectomy under these circumstances, we developed a transumbilical laparoendoscopic single-site (TU-LESS) extraperitoneal approach for lymphadenectomy. In this research, the primary goal is to demonstrate the feasibility of the novel approach in systematic lymphadenectomy and present the surgical process step-by-step. Methods: Between May in 2020 to June in 2021, patients who had the indications of systematic lymphadenectomy underwent lymphadenectomy via the TU-LESS extraperitoneal approach. This new approach was described in detail, and the clinical characteristics and surgical outcomes were collected and analyzed. Results: Eight patients with gynecological carcinoma were included in the research, including four with high-risk endometrial cancer and four with early-stage ovarian cancer. The TU-LESS extraperitoneal approach for pelvic and para-aortic lymphadenectomy was successfully performed in all patients without conversion. In all, a median of 26.5 pelvic lymph nodes (range 18 - 35) and 18.0 para-aortic lymph nodes (range 7 - 43) were retrieved. There was a median of 166.5 minutes of surgical time (range 123 - 205). Patients had speedy recoveries without complications. All patients had positive pain responses after surgery, as well as satisfactory cosmetic and body image outcomes. Conclusion: Our initial experience showed that it is feasible to perform systematic lymphadenectomy with the TU-LESS extraperitoneal approach. And this new approach may provide a new measure or a beneficial supplement for lymphadenectomy in gynecologic cancer.